Criminological portrait of a professional criminal - N. K. Makarenko (Bulletin of Kharkiv National University of Internal Affairs)
The article reveals the peculiarities of criminological characteristics of professional criminals. It is indicated that professional criminals have deliberately chosen criminal activity as a tool to meet their material needs. The main motive of a professional criminal is profit, which is based on improving the material standard of living and obtaining a constant income from criminal activity. It is established that professional criminals are a group of the most dangerous and active criminals who deliberately oppose themselves to society and have a significant deformation of the value and normative sphere.